Genetic analysis of a SARS-CoV-2 Omicron variant from a Chinese traveller returning from overseas. Issue 1 (31st December 2022) - Jia, Hongling; Wang, Hui; Cao, Lan; Lai, Zhisheng; Cheng, Zichun; Chen, Qingpei; Liu, Tongzheng; Liu, Xiangyi; Wen, Yanting; Xu, Conghui; Lu, Weizhi; Yang, Guang; et al.
ABSTRACT: Since the SARS-CoV-2 Omicron variant was first reported from South Africa, it has rapidly spread in over 100 countries. Only two cases infected by the Omicron variant were recently identified in China. The one case in Guangzhou has a relatively long incubation time and mild symptoms. Analysis of the complete viral genome sequence shows three missing Omicron unique mutations and one additional mutation in the newly characterized genome. These unique mutations may be related to the clinical presentation in this case.